A longitudinal study of diurnal cortisol patterns and associated factors in breast cancer patients from the transition stage of the end of active cancer treatment to post-treatment survivorship. (December 2017) - Hsiao, Fei-Hsiu; Jow, Guey-Mei; Kuo, Wen-Hung; Wang, Ming-Yang; Chang, King-Jen; Lai, Yu-Ming; Chen, Yu-Ting; Huang, Chiun-Sheng
Abstract: Objectives: The aim of this study was to examine the changes in diurnal cortisol patterns and its associated factors among breast cancer patients over a 14-month follow up period. Materials and methods: A total of 85 breast cancer patients were recruited to participate in this study. Assessments were performed at baseline (T0), T1 (the 2nd month), T2 (the 5th month), T3 (the 8th month), and T4 (the 14th month). Salivary cortisol was measured and the following questionnaires were administered: BDI-II depression scale, European Organization for Research and Treatment of Cancer Core Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and its breast cancer-specific complementary measure (EORTC QLQ-BR23). Patients were grouped into flat and steep groups, according to the median of the diurnal cortisol slopes at the time of the transition period. Results: Breast cancer patients in the flatter slope group at transition period demonstrated steeper slopes over the course of recovery from treatment and those in the steeper slope group at transition period continued with steeper slopes over the course of recovery. The greater breast cancer-related symptoms (side-effects, symptoms relating to breast and arm, and hair loss) were associated with the changes in flatter diurnal cortisol slopes during14-month follow up period. Conclusion: Diurnal cortisol patterns in flatter slope group at the transition period appear to have a trend of recovery with the passage of time over the course of recovery from treatment. Management of breast cancer symptoms could improve dysregulation of diurnal cortisol patterns among survivors. Highlights: Flatter diurnal cortisol patterns have a trend of recovery from treatment. Steeper diurnal cortisol patterns maintain stable over 14 months. Breast cancer-related symptoms predict the recovery of diurnal cortisol patterns.